2018
DOI: 10.1161/atvbaha.118.311222
|View full text |Cite
|
Sign up to set email alerts
|

IgE to the Mammalian Oligosaccharide Galactose-α-1,3-Galactose Is Associated With Increased Atheroma Volume and Plaques With Unstable Characteristics—Brief Report

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(82 citation statements)
references
References 20 publications
4
76
1
1
Order By: Relevance
“…Allergen-positive patients have been identified to have higher titers of anti-gal IgG, with more IgG subtype 1 and less IgG subtype 2 than allergen negative populations 44 . Furthermore, allergen-positive patients manifest a significant difference in coronary artery disease when compared to an allergen-negative cohort 38 . This suggests that IgE sensitization to alpha gal may be a novel modifiable risk factor for coronary atherosclerosis, especially in patients 65-years and younger.…”
Section: Prevalence Of Ige Anti-gal Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Allergen-positive patients have been identified to have higher titers of anti-gal IgG, with more IgG subtype 1 and less IgG subtype 2 than allergen negative populations 44 . Furthermore, allergen-positive patients manifest a significant difference in coronary artery disease when compared to an allergen-negative cohort 38 . This suggests that IgE sensitization to alpha gal may be a novel modifiable risk factor for coronary atherosclerosis, especially in patients 65-years and younger.…”
Section: Prevalence Of Ige Anti-gal Antibodiesmentioning
confidence: 99%
“…The reported prevalence of individuals in the United States with elevated allergen-specific titers of anti-gal IgE (i.e. allergen positive) has been reported to be in the range of 8% to 46%, with highest prevalence within the geographic distribution of the Lone Star tick ( Figure 1) 21,[38][39][40][41] . Similar prevalence rates have been reported in other regions around the world (Table 1) 27,42,43 .…”
Section: Prevalence Of Ige Anti-gal Antibodiesmentioning
confidence: 99%
“…6 Wilson et al showed that individuals with IgE antibodies against α-Gal develop bigger atheroma plaques. 7 They suggest that chronic ingestion of α-Gal-carrying mammalian products, especially glycolipids, might cause the release of inflammatory products from mast cells bearing anti-α-Gal IgE antibodies and that this might lead to the formation of bigger plaques. In addition, they suggest that other cells might also be involved in the development of atheroma plaques and that this could happen via the binding of anti-α-Gal IgG1 antibodies to mammalian glycolipids.…”
Section: Our Data Showing the Presence Of High Amounts Of α-Gal-specificmentioning
confidence: 99%
“…In a cohort of adults who were enrolled without regard to allergic history, we recently reported that the severity of coronary artery disease was greater in subjects who were sensitized to a-Gal. 50 This finding prompts several questions but raises the possibility that IgE to glycolipid food allergens could have severe long-term consequences in addition to their contribution to anaphylaxis. Our working hypothesis is that chronic consumption of mammalian products could act in an antigen-dependent manner to stimulate tissue-resident mast cells, including those in the walls of coronary arteries, in subjects who make IgE to a-Gal.…”
Section: Recent Insights Into Food Allergymentioning
confidence: 99%